2022
DOI: 10.3389/fpls.2021.752683
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Rhizosphere Soil and Root Endophytic Microbial Communities Associated With Root Rot of Panax notoginseng

Abstract: Panax notoginseng (Burk.) F. H. Chen is a Chinese medicinal plant of the Araliaceae family used for the treatment of cardiovascular and cerebrovascular diseases in Asia. P. notoginseng is vulnerable to root rot disease, which reduces the yield of P. notoginseng. In this study, we analyzed the rhizosphere soil and root endophyte microbial communities of P. notoginseng from different geographical locations using high-throughput sequencing. Our results revealed that the P. notoginseng rhizosphere soil microbial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 117 publications
0
15
0
Order By: Relevance
“…Besides this, some bacteria in the commonly dominant genera displayed biological control functions for plant disease. For example, Pseudomonas can produce the antifungal compound 2,4-diacetylphloroglucinol [ 5 ], while Variovorax paradoxus can help Panax notoginseng resist root rot disease [ 45 ]. Similarly, Penicillium can produce antibiotic-like substances that protect plants from attacks by pathogens [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, some bacteria in the commonly dominant genera displayed biological control functions for plant disease. For example, Pseudomonas can produce the antifungal compound 2,4-diacetylphloroglucinol [ 5 ], while Variovorax paradoxus can help Panax notoginseng resist root rot disease [ 45 ]. Similarly, Penicillium can produce antibiotic-like substances that protect plants from attacks by pathogens [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Micromonospora , Burkholderiales , and Anaerolinea are related to the N and C cycles ( 27 29 ), and Saccharothrix can generate chitinase and degrade the structure of plant-pathogenic fungi ( 30 ). For their part, genera such as Rhodopseudomonas , Actinoplanes , Burkholderia , and Variovorax paradoxus , which are present in the rhizosphere soil, can help Panax notoginseng resist the invasion of root rot disease ( 31 ). Consistently, the results reported herein highlighted the fact that the increased relative abundance of Bradyrhizobium , Micromonospora , Burkholderiales , and Anaerolinea may enhance the N and C cycles, thereby providing more available nutrients to invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of the soil microbial community in P. notoginseng is not lower than the diversity of endophytic microorganisms, which is an important source of BCAs for P. notoginseng disease (Wang, Yang, et al, 2022). Xu et al (2019) found that echinosporin and 7-deoxychinosporin from Actinomycete strain YIM PH20520 exhibited good antifungal activity.…”
Section: The Role Of Beneficial Microorganismsmentioning
confidence: 99%
“…The diversity of the soil microbial community in P. notoginseng is not lower than the diversity of endophytic microorganisms, which is an important source of BCAs for P. notoginseng disease (Wang, Yang, et al., 2022 ). Xu et al.…”
Section: Biological Control Of Root Rot In P Notoginsengmentioning
confidence: 99%